The design thinking toolbox : a guide to mastering the most popular and valuable innovation methods - Lewrick, Michael; Link, Patrick, 1968-; Leifer, Larry J. (John Wiley & Sons, Inc., 2020)
"Encyclopedia of Design Thinking Tools explains the most important tools and methods over the Design Thinking cycle. Based on the largest international survey on the use of Design Thinking Tools and Methods, the most popular methods are described on four pages each, by an expert from the Design Thinking community. Simple instructions, expert tips, templates and images of the application make the Encyclopedia valuable reading, especially for Design Thinking beginners. It is suitable for design thinkers who want to quickly and comprehensively familiarize themselves with the tools and try out new tools. It helps readers with: selecting the right tools and finding new tools planning training/workshops on design thinking practical application tips This is an encyclopedia that is the perfect complement to the bestselling, The Design Thinking Playbook"-- Provided by publisher.
Keywords: Problem solving.; Creative thinking.; Project management.; Creative ability in technology.; Creative ability in business.; elektronické knihy; electronic books